ENDOMETRIAL POLYP AND CEHM PYOMETRA COMPLEX IN A DOG - JAYAKUMAR, C; KANTHARAJ, S; SUDHA, G; KRISHNASWAMY, A (The Indian Journal of Animal Reproduction, 2023)
The current report describes an endometrial polyp and cystic endometrial hyperplasia-pyometra complexin a ten year old female Labrador dog.
Keywords: Endometrial polyp; CEH-pyometra